Carvedilol for primary prophylaxis of variceal bleeding in cirrhotic patients with haemodynamic non-response to propranolol. Issue 11 (18th December 2012) - Reiberger, Thomas; Ulbrich, Gregor; Ferlitsch, Arnulf; Payer, Berit Anna; Schwabl, Philipp; Pinter, Matthias; Heinisch, Birgit B; Trauner, Michael; Kramer, Ludwig; Peck-Radosavljevic, Markus; ,
Abstract : Objective: Non-selective β-blockers or endoscopic band ligation (EBL) are recommended for primary prophylaxis of variceal bleeding in patients with oesophageal varices. Additional α-adrenergic blockade (as by carvedilol) may increase the number of patients with haemodynamic response (reduction in hepatic venous pressure gradient (HVPG) of ≥20% or to values <12 mm Hg). Design: Patients with oesophageal varices undergoing measurement of HVPG before and under propranolol treatment (80–160 mg/day) were included. HVPG responders were kept on propranolol (PROP group), while non-responders were placed on carvedilol (6.25–50 mg/day). Carvedilol responders continued treatment (CARV group), while non-responders to carvedilol underwent EBL. The primary aim was to assess haemodynamic response rates to carvedilol in propranolol non-responders. Results: 36% (37/104) of patients showed a HVPG response to propranolol. Among the propranolol non-responders 56% (38/67) eventually achieved a haemodynamic response with carvedilol, while 44% (29/67) patients were finally treated with EBL. The decrease in HVPG was significantly greater with carvedilol (median 12.5 mg/day) than with propranolol (median 100 mg/day): −19±10% versus −12±11% (p<0.001). During a 2 year follow-up bleeding rates for PROP were 11% versus CARV 5% versus EBL 25% (p=0.0429). Fewer episodes of hepatic decompensation (PROP 38%/CARV 26% vs EBL 55%; p=0.0789) and significantly lower mortality (PROP 14%/CARV 11% vs EBL 31%; p=0.0455) were observed in haemodynamic responders compared to the EBL group. Conclusions: Carvedilol leads to a significantly greater decrease in HVPG than propranolol. Using carvedilol for primary prophylaxis a substantial proportion of non-responders to propranolol can achieve a haemodynamic response, which is associated with improved outcome with regard to prevention of variceal bleeding, hepatic decompensation and death.